Application of the Scramble Method to Improve the Initial Reading Skills of Class II Students at SD Negeri 024 Rambah Samo - Efendi, Rinja; Sari, Nauli Tama (STKIP Rokania Pasir Pangaraian, 2023)
This research aims to improve students' initial reading skills using the scramble method for class II SD Negeri 024 Rambah Samo. This type of research is classroom action research conducted collaboratively and participatively. The subjects in this research were 19 class II students at SD Negeri 024 Rambah Samo, consisting of 12 female students and 7 male students. This research was carried out in two cycles. Each cycle consists of two meetings. Data collection techniques are carried out by observation, tests and documentation. The data analysis technique used is quantitative descriptive data analysis. Based on the research results, it can be concluded that the application of the scramble method can improve the initial reading skills of class II students at SD Negeri 024 Rambah Samo in the first cycle by 63.16% and increase in the second cycle by 84.22%.